Cadmium-Induced Upregulation of Lipid Peroxidation and Reactive Oxygen Species Caused Physiological, Biochemical, and Ultrastructural Changes in Upland Cotton Seedlings. (26th December 2013) - Khan, Muhammad Daud; Mei, Lei; Ali, Basharat; Chen, Yue; Cheng, Xin; Zhu, S. J.
Abstract : Cadmium (Cd) toxicity was investigated in cotton cultivar (ZMS-49) using physiological, ultrastructural, and biochemical parameters. Biomass-based tolerance index decreased, and water contents increased at 500 μ M Cd. Photosynthetic efficiency determined by chlorophyll fluorescence and photosynthetic pigments declined under Cd stress. Cd contents were more in roots than shoots. A significant decrease in nutrient levels was found in roots and stem. A significant decrease in nutrient levels was found in roots and stems. In response to Cd stress, more MDA and ROS contents were produced in leaves than in other parts of the seedlings. Total soluble proteins were reduced in all parts except in roots at 500 μ M Cd. Oxidative metabolism was higher in leaves than aerial parts of the plant. There were insignificant alterations in roots and leaves ultrastructures such as a little increase in nucleoli, vacuoles, starch granules, and plastoglobuli in Cd-imposed stressful conditions. Scanning micrographs at 500 μ M Cd showed a reduced number of stomata as well as near absence of closed stomata. Cd depositions were located in cell wall, vacuoles, and intracellular spaces using TEM-EDX technology. Upregulation of oxidative metabolism, less ultrastructural modification, and Cd deposition in dead parts of cells show that ZMS-49 has genetic potential to resist Cd stress, which need to be explored.